Understanding the Role of Housing in Inequality and Social Mobility - Yang Tang; Xinwen Ni (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2019)
Housing typically takes up a major proportion of households' expenditure, and thus it certainly plays a critical role in shaping the pattern of income inequality and social mobility. Whether high housing price-to-rent ratio will am- plify inequality and inhibit social class upgrading is still a controversial issue in the existing literature. In this paper, we develop a partial equilibrium life- cycle framework to address these issues. Agents in our economy are divided into two social classes according to the initial human capital level inherited from their parents. Those who belong to upper class will draw their innate abilities from a distribution that rst order stochastically dominates those from lower class. Throughout the entire lifecycle, agents make endogenous human capital investment and housing tenure decisions. We calibrate the model to mimic some stylized facts in the the real world counter part. Our simulation results indicate an inverse-U pattern between housing price-to-rent ratio and measures of income inequality, and as well as a U-shape pattern between price- to-rent ratio and social mobility measured by Shorrocks Index. The implication is that housing tends to amplify the inequality and slow down the social mobility when houses can only be purchased by a small group of agents in the economy. Moreover, our results also suggest that better quality of education as a result of a higher return to human capital investment tends to dampen the role of housing.
Keywords: C00; 330; Income Inequality; Social Mobility; Price-to-rent ratio